MALI (African Disability Rights Yearbook, 2021)
According to the World Health Organization (WHO), the Malian population is 18,1 million. Persons with disabilities are 2 247 500, that is 15% of the total population. According to the 2003 household survey, the most prevalent forms of disabilities include visual, motor disabilities, cerebral driving handicap, intellectual disabilities and psychosocial handicap and albinism. The Republic of Mali signed and ratified the United Nations Convention on the Rights of Persons with Disabilities (CRPD), as well as its Optional protocol on 15 May 2007. The CRDP and the Optional Protocol have been ratified on 7 April, 2008. Through the CRDP Art. 35, the Republic of Mali was supposed to submit its country report on 24 June 2019. Through Art. 2 the Constitution of Mali, all Malians are born and remain free and equal in rights and duties. Any discrimination based on disability is therefore prohibited. In addition, the Constitution indirectly addresses disabilities through Art. 1 affirms that ‘the human person is sacred and inviolable. Every individual has the Right to life, liberty, security and integrity of his or her person. The Republic of Mali has an important pieces of legislation that directly address disability. The key one is the Law 2018-027, of 12 June 2018 on the Rights of Persons with Disabilities. The policies that directly address persons with disabilities are: The Policy of Solidarity (since 1993) which aims to reduce inequalities, provide social protection and promote the socio-economic development of vulnerable groups such as persons with disabilities and the National Special Education Policy (1999). Mali has the following programmes: The National program of Rehabilitation on Community Basis (RBC) since 1998 is to raise the awareness of families of children with disabilities, their rehabilitation and their rehabilitation at home; the Health and Social Development Program, the Ten-Year Health and Social Development Plan (2014-2023); and the Strategic Plan for the Promotion of Persons with Disabilities (2015-2024). Other than ordinary courts or tribunals, the Republic of Mali does not have an official body which specifically addresses the violation of the Rights of people with disabilities. The Republic of Mali has a National Human Rights Commission, since 2016. There are numerous organisations that represent and advocate for the rights and welfare of persons with disabilities in Mali, represented by the Malian Federation of Associations of Disabled persons which is an umbrella body of around 20 organisations. In Mali, the Ministry of Solidarity and Humanitarian Action is in charge of people with disabilities. The Ministry develops and implements policies and strategies in favour of disabled people. Persons with disabilities encounter multiple levels of exclusion and discrimination. As far as access is concerned, although laws provide for access to public buildings, employment, in practice, very little is done to ensure access for persons with disabilities. The Republic of Mali should conduct reliable specific household census of persons with disabilities, taking into account women, children and elderly persons with disabilities.
Keywords: Malian population; prevalent forms of disabilities; access; policies